Esophageal cancer as initial presentation of Fanconi anemia in patients with a hypomorphic FANCA variant - Lach, Francis P. (Cold Spring Harb Mol Case Stud, 2020)
Fanconi anemia (FA) is a clinically heterogenous and genetically diverse disease with 22 known complementation groups (FA-A to FA-W), resulting from the inability to repair DNA interstrand cross-links. This rare disorder is characterized by congenital defects, bone marrow failure, and cancer predisposition. FANCA is the most commonly mutated gene in FA and a variety of mostly private mutations have been documented, including small and large indels and point and splicing variants. Genotype–phenotype associations in FA are complex, and a relationship between particular FANCA variants and the observed cellular phenotype or illness severity remains unclear. In this study, we describe two siblings with compound heterozygous FANCA variants (c.3788_3790delTCT and c.4199G > A) who both presented with esophageal squamous cell carcinoma at the age of 51. The proband came to medical attention when he developed pancytopenia after a single cycle of low-dose chemotherapy including platinum-based therapy. Other than a minor thumb abnormality, neither patient had prior findings to suggest FA, including normal blood counts and intact fertility. Patient fibroblasts from both siblings display increased chromosomal breakage and hypersensitivity to interstrand cross-linking agents as seen in typical FA. Based on our functional data demonstrating that the c.4199G > A/p.R1400H variant represents a hypomorphic FANCA allele, we conclude that the residual activity of the Fanconi anemia repair pathway accounts for lack of spontaneous bone marrow failure or infertility with the late presentation of malignancy as the initial disease manifestation. This and similar cases of adult-onset esophageal cancer stress the need for chromosome breakage testing in patients with early onset of aerodigestive tract squamous cell carcinomas before platinum-based therapy is initiated.